PENINGKATAN EDUKASI EKONOMI KREATIF MELALUI PENGOLAHAN KRIPIK “PISITAKE” DI DESA RACEK KECAMATAN TIRIS KABUPATEN PROBOLINGGO. - Q, Nanang; Muni, Abd (KHIDMAH : Jurnal Pengabdian Masyarakat, 2021)
Abstract The assistance provided is to utilize local raw materials that do not have a high selling value, such as bananas, cassava, cassava and taro. Assistance is carried out starting from the selection of raw materials until the production process is complete to marketing. The processing results become chips and can add economic value to the surrounding community. The purpose of this community service is to provide knowledge to the community about entrepreneurship how to process local raw materials "PISATAKE" (bananas, cassava, taro, and cassava) into local products that have added and economic value. The method used in this community service is a participatory training method. namely involving as many partners as possible in the activities of lectures, discussions, and practices that produce products. Shaping the character of students as businessmen and planning the products to be produced which they then analyze from the aspects of the strengths and weaknesses of the product and the procedures for marketing the product. The results of this assistance can add insight and experience for individuals and community groups, can open entrepreneurship. Mapping of productive raw material producing locations in Racek Village. Local ingredients whose quality has been determined will be processed to be processed into ready-to-eat ingredients in the form of PISITAKE chips (banana, cassava, cassava and taro) which can then be able to absorb community labor and increase people's income. Keywords: Creative Economy and Pisitake Chips